Efficient removal of heavy metals from aqueous solutions by Mg/Fe bimetallic oxide-modified biochar: Experiments and DFT investigations. (1st June 2023) - Cheng, Song; Meng, Weibo; Xing, Baolin; Shi, Changliang; Wang, Qiang; Xia, Daping; Nie, Yanhe; Yi, Gunyun; Zhang, Chuanxiang; Xia, Hongying
Abstract: Mg/Fe bimetallic oxide-modified biochar (Fe/Mg-BC) derived from Eupatorium adenophorum was prepared by the co-pyrolysis of magnesium nitrate and ferric chloride for Pb(II) and Cd(II) removal from wastewater. The physicochemical properties of the Fe/Mg-BC were analyzed by several characterization methods such as XRD, XPS, SEM and FTIR. Pb(II) and Cd(II) adsorption amounts of Fe/Mg-BC in monometallic systems is larger than those in bimetallic systems owing to competitive adsorption. The adsorption mechanism analysis indicated that ion exchange and mineral precipitation were responsible for Pb(II) and Cd(II) adsorption. The overlap of electron clouds and orbits between MgO and Pb(II) is denser than that of Cd(II), indicating that Fe/Mg-BC has a stronger affinity for Pb(II) than for Cd(II) based on density functional theory calculations. The reusability result indicates that Fe/Mg-BC shows excellent Pb(II) and Cd(II) adsorption performance. Fe/Mg-BC presented remarkable adsorption capability, excellent recoverability, and high throughput, indicating its potential application in the treatment of wastewater containing heavy metals.